The midthigh pull: Proper application and progressions of a weightlifting movement derivative - DeWeese, B. H.; Serrano, A. J.; Scruggs, S. K.; Burton, J. D (Strength and Conditioning Journal, 2013)
The clean grip midthigh pull and snatch grip midthigh pull are exercises that focus on reinforcing the double knee bend and triple extension involved in weightlifting movements. As a result, these pulling movements are used with the purpose of making an athlete more efficient at producing force with an overload stimulus in the peak power position. In addition, these exercises can be used as a teaching modality for the progressive development of the full clean or snatch.